The effects of a socially evaluated cold press stressor on inhibitory gating, bradykinesia, and tremor in persons with Parkinson’s disease - Zaman, Andrew; Jewell, Crystal; Izbicki, Patricia; Stegemöller, Elizabeth L. (Frontiers in Human Neuroscience, 2025)
IntroductionImpaired inhibitory gating is a sensory processing symptom of Parkinson’s disease (PD) that may be associated with bradykinesia and motor inhibition. Acute stress impairs inhibitory gating in healthy adults; however, it is unclear how stress impacts inhibitory gating in people with PD.MethodsUsing a Socially Evaluated Cold Pressor (SECP) to induce acute physical stress, inhibitory gating was assessed through electroencephalography (EEG) in eight individuals diagnosed with PD and 11 age- and gender-matched healthy older adults (HOAs) by measuring the p50 ratio during an auditory paired click paradigm. Kinematic measures of bradykinesia and tremor were also collected.ResultsResults confirmed decreased inhibitory gating [F(1,17) = 12.813, p = 0.002, ηp2 = 0.430], decreased finger tapping amplitude [F(1,27) = 7.420, p = 0.011, ηp2 = 0.216], and increased postural tremor amplitude [F(1,27) = 6.676, p = 0.016, ηp2 = 0.198] in both persons with PD and HOAs following the induction of an acute physical stressor, with larger differences in persons with PD. Moreover, decreases in inhibitory gating were significantly related to changes in finger tapping amplitude and postural tremor amplitude.DiscussionThese findings provide evidence to suggest that stress impairs both inhibitory gating and some motor impairments in persons with PD, and that these impairments may be related. These results add to the limited literature in understanding the effects of stress on PD symptoms and may inform future potential clinical targets for therapeutics.